Does breastfeeding influence the risk of developing diabetes mellitus in children? A review of current evidence - Patrícia F. Pereira; Rita de Cássia G. Alfenas; Raquel Maria A. Araújo (Jornal de Pediatria (Versão em Português), 2014)
Objective: The aim of this study was to perform a review to investigate the influence of breastfeeding as a protective agent against the onset of diabetes in children. Sources: Non-systematic review of SciELO, LILACS, MEDLINE, Scopus, and VHL databases, and selection of the 52 most relevant studies. A total of 21 articles, specifically on the topic, were analyzed (nine related to type 1 diabetes and 12 to type 2 diabetes). Data synthesis: The duration and exclusivity of breastfeeding, as well as the early use of cow's milk, have been shown to be important risk factors for developing diabetes. It is believed that human milk contains substances that promote the maturation of the immune system, which protect against the onset of type 1 diabetes. Moreover, human milk has bioactive substances that promote satiety and energy balance, preventing excess weight gain during childhood, thus protecting against the development of type 2 diabetes. Although the above mentioned benefits have not been observed by some researchers, inaccuracies on dietary habit reports during childhood and the presence of interfering factors have been considered responsible for the lack of identification of beneficial effects. Conclusion: Given the scientific evidence indicated in most published studies, it is believed that the lack of breastfeeding can be a modifiable risk factor for both type 1 and type 2 diabetes. Strategies aiming at the promotion and support of breastfeeding should be used by trained healthcare professionals in order to prevent the onset of diabetes.